New cellulosic fibre from Spathes of male date for lightweight composite materials: extraction and characterization - Lamia, Benhamadouche; Nafissa, Moussaoui; Abdelouahab Djoubair, Benhamadouche; Jawaid, Mohammad; Fouad, Hassan; Midani, Mohamad (Elsevier, 2023)
Researchers and industry are looking for green and sustainable materials as reinforcement for lightweight composite structures. This research aim was designed to study the characteristics of the fibre extracted from a waste product of the spathe of date palm (SDP). In this work, density, crystallinity index, crystal size, tensile strength, surface roughness, extreme degradation temperature and thermal stability of SDP fibres were investigated. Density is estimated to be 0.59 g/cm3. X-ray diffraction analysis indicated the crystallinity index about (57.82%) and the crystal size is (19 nm). The results of the thermal analysis gave the degradation temperature as 270 °C and Ea as 69.14 kJ/mol. Scanning electron microscopy (SEM) investigation confirmed the presence of surface contaminants including wax and other foreign materials. Also, the mechanical properties identified are tensile strength (100 ± 21.5 MPa), and Young's modulus (4 ± 0.9% GPa). Based on the study's findings, SDP fibres should be considered for usage as a reinforcing material in the development of novel polymer composites with a wide range of lightweight industrial applications.